An Analytical Study of Traffic Volume and Noise Level in Lucknow City - Prasad, Dipak; Sanyal, Srabani (National Geographical Journal of India, 2022)
Increasing emission from vehicular traffic, industry and other human activities possess potential risks of increasing noise level in urban areas. In India, the number of registered vehicles was 0.3 million in 1951 which increased to 142 million by, 2011. As a result noise level in many Indian cities are above the permissible limit of NAAQS, like in Lucknow city, (26º30' N to 27º10' N latitude and 80º30' E to 80º13' E longitude) with average noise with of 78.5 dB(A). According to recent epidemiological studies more than thousands of premature deaths and health related problems are attributed to increasing noise level. The assessment of noise pollution is important for understanding the nature of ambient noise and its relation with traffic volume. In this paper an attempt has been made to analytically study the traffic and noise level in Lucknow city. It is obvious from the result acquired through the statistical analysis that traffic volume is positively correlated with noise generated in specific areas. It is apparent from the study that there is a need for proper traffic management, abetment of law and involvement of people in mitigating the problem.